Using development to achieve stability, and stability to promote rapid and sustainable development of the country: A breakthrough in the Party’s developmental thinking at the 14th National Congress - VŨ VĂN HÀ (Political Theory Journal, 2026)
The article analyzes the evolution of the Party’s developmental thinking over 40 years of national renovation, moving from the requirement of maintaining stability for development to the guideline of using development to achieve stability, and stability to promote rapid and sustainable development of the country. By clarifying this breakthrough in developmental thinking at the 14th National Party Congress, the article identifies several emerging issues regarding perception, institutions, risk management, social justice, and public trust, thereby proposing solutions to realize this developmental viewpoint in the new era.